Javno dobro, skupni viri in skupno - Šmid Hribar, Mateja (Urbani izziv, 2018)
This article aims to study and clearly define the terms public good, common-pool resources, and the commons. Using path dependency analysis, interviews, and workshops among the general public and experts, we highlight the perception of public goods and the commons in Slovenia as a transitional society. The analysis reveals that the general public%s understanding of these terms is still strongly influenced by communist socialist-era emphasis on social justice, equality, and access to goods for everyone, which can be at odds with the right to private property. Inadequate governance of goods that are considered public goods, but are in fact common-pool resources, can lead to conflicts and degradation of common-pool resources, which results in the loss of advantages providing wellbeing. Because people%s lives depend on subtractable natural resources, it is necessary to raise awareness about them among the general public and professional community, emphasize their vulnerability, and explain that they cannot be accessible to anyone in unlimited quantities. Furthermore, in an international context, using the Slovenian case, we seek to improve the understanding of human behaviour and expectations concerning public goods and common-pool resources in post-communist transitional societies.
Keywords: common good; common property; common-pool resources; commons; governance; javno dobro; management; prostor; public good; skupna lastnina; skupni viri; skupno; skupno dobro; Slovenia; Slovenija; space; transitional society; tranzicijska družba; upravljanje